ANALISIS FAKTOR PENYEBAB KESULITAN SISWA DALAM MENYELESAIKAN SOAL LITERASI BERBASIS TEKS BACAAN PADA SISWA KELAS IV SD NEGERI 060886 KOTA MEDAN - Hanna Putri Syahkira; Dian Armanto; Anita Yus (STKIP Subang, 2026)
Elementary school students often experience difficulties in solving literacy problems based on reading texts. These problems indicate that students still struggle to understand text content, answer questions, and interpret information from reading passages. This study aims to analyze the factors causing these difficulties among fourth-grade students at SD Negeri 060886 Medan. This research employed a qualitative approach with a descriptive method. The subjects were fourth-grade students. Data were collected through essay tests to assess students’ comprehension of reading texts. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results showed that students’ difficulties were influenced by several factors, including low reading ability, limited comprehension of text content, limited vocabulary, and low reading interest. In addition, external factors such as lack of variation in teaching methods and limited literacy practice also affected students' abilities. The most dominant factor was students’ low reading comprehension ability.